Literacy Class: Instructional Design at High School - Vanira Rima Shinta; Riche Cynthia Johan; Lien Halimah (Record and Library Journal, 2023)
Background of the study: Literacy is an activity that can improve one's abilities and skills in terms of thinking capability and understanding information more skillfully. Literacy can increase reading interest. Something that can develop this is the existence of a school literacy movement that is aimed especially at students to be able to expand a school literacy culture. Purpose: This research aims to find out how to implement and evaluate student literacy activities at Alfa Centauri High School. Method: The methods used are descriptive qualitative methods with the ADDIE instructional design model. The technique of data collection used was an interview. The informant in this study was the leader of the Alfa Centauri High School literacy team. Findings: The results obtained are SMA Alfa Centauri implements literacy activities through three stages reading activities and creative writing activities. Conclusion: SMA Alfa Centauri is considered to have been able to implement literacy activities well and effectively in increasing students' reading interests. That can be visible from the program development, product results, and achievement in the implemented programs.